Фармакогностичне дослідження культивованих видів роду Primula L. - Сініченко, А. В.; Синиченко, А. В.; Sinichenko, A. V. (Запорізький державний медичний університет, 2020)
Уперше проведено комплексне фармакогностичне дослідження трьох культивованих видів роду Primula L. (примули зубчастої (дрібнозубчастої) – Primula denticulatа Smith, примули Юлії – Primula juliae Kusn., примули скельної – Primula saxatilis Коm.). У досліджуваних об’єктах встановлено якісний склад і визначено кількісний вміст кислот органічних та аскорбінової, вуглеводів, жирних кислот, амінокислот, речовин фенольного характеру (кислот гідроксикоричних, флавоноїдів, кумаринів, конденсованих дубильних речовин, антоціанів), тритерпенових сапонінів. Уперше проведено системне морфолого-анатомічне дослідження примули зубчастої, п. Юлії та п. скельної стебла, квітки, листка та кореневища з коренями, встановлено їх макро- і мікродіагостичні ознаки. Одержано субстанції – густі екстракти з примули зубчастої листків і кореневищ з коренями. Встановлено безпечність даних екстрактів: за дослідженням гострої токсичності їх віднесено до V класу токсичності за класифікацією К. К. Сидорова (практично нетоксичні речовини – ЛД50 ≥ 5000 мг/кг). Визначено антиексудативну активність одержаних екстрактів, найвищу активність проявив густий екстракт з примули зубчастої листків. Досліджено виразну відхаркувальну активність у густого екстракту з примули зубчастої кореневищ з коренями, що була аналогічна активності референс-препарату – краплям «Геделікс». Досліджено антимікробну активність отриманих субстанцій. Доведено, що виражену бактерицидну дію проявляє густий екстракт з примули зубчастої листків по відношенню до Staphylococcus aureus, Staphylococcus epidermidis та Corynebacterium spp. Розроблено проекти методів контролю якості «Примули зубчастої кореневища з коренями», «Примули зубчастої листки», «Примули скельної кореневища з коренями», «Примули скельної листки», «Примули Юлії кореневища з коренями», «Примули Юлії листки», «Примули зубчастої листків екстракт густий» та «Примули зубчастої кореневищ з коренями екстракт густий». Впервые проведено комплексное фармакогностическое исследование трех культивируемых видов рода Primula L. – Primula denticulatа Smith, Primula juliae Kusn., Primula saxatilis Коm. В исследуемом сырье установлен качественный состав и определено количественное содержание кислот органических и аскорбиновой, углеводов, жирных кислот, аминокислот, фенольных веществ (кислот гидроксикоричных, флавоноидов, кумаринов, конденсированных дубильных веществ, антоцианов), тритерпеновых сапонинов. Впервые проведено системное морфолого-анатомическое исследование примулы зубчатой, п. Юлии и п. скальной стебля, цветка, листка и корневищ с корнями, установлено их макро- и микродиагностические признаки. Получены субстанции – густые экстракты из листьев и корневищ с корнями примулы зубчатой. Установлено безопасность данных экстрактов: по исследованиям острой токсичности они отнесены к V классу токсичности по классификации К. К. Сидорова (практически нетоксичные вещества – ЛД50 ≥ 5000 мг/кг). Определена антиэкссудативная активность густых экстрактов из примулы зубчатой листьев и корневищ с корнями, установлено, что самую высокую активность проявил густой экстракт из примулы зубчатой листьев. Исследована выразительная отхаркивающая активность густого экстракта примулы зубчатой корневищ с корнями, которая была аналогична активности референс-препарата – каплям «Геделикс». Исследована антимикробная активность полученных субстанций. Доказано, что выраженное бактерицидное действие проявляет густой экстракт примулы зубчатой листьев по отношению к Staphylococcus aureus, Staphylococcus epidermidis и Corynebacterium spp. Разработаны проекты методов контроля качества «Примулы зубчатой корневища с корнями», «Примулы зубчатой листья», «Примулы скальной корневища с корнями», «Примулы скальной листья», «Примулы Юлии корневища с корнями», «Примулы Юлии листья», «Примулы зубчатой листьев экстракт густой» и «Примулы зубчатой корневищ с корнями экстракт густой». The systematic pharmacognostical study of over ground and underground organs of three cultivated species of the genus Primula L. (drumstick primrose – Primula denticulate Smith, Julia’s primrose – Primula juliae Kusn., rock primrose – Primula saxatilis Kom.) was carried out for the first time. For the studied objects, we have determined qualitative and quantitative composition of the major groups of BAS: ascorbic and organic acids, carbohydrates, amino and fatty acids, phenolic substances (hydroxycinnamic acids, flavonoids, coumarins, condensed tannins, anthocyanins), triterpenoid saponins. By the spectrophotometric method for the over ground and underground organs of investigated plant raw materials we have determined the quantitative content of ascorbic acid and free organic acids. The amount of free organic acids was in the drumstick primrose, Julia’s primrose, rock primrose leaves 1,97 %, 1,48 %, 2,01 % respectively; in the flowers – 1,68 %, 1,33 %, 1,75 % respectively; in the rhizomes with roots – 1,33 %, 1,01 %, 1,34 % respectively. The content of ascorbic acid in the drumstick primrose, Julia’s primrose, rock primrose leaves was 1,19 %, 1,46 %, 1,55 %; in the flowers – 0,72 %, 1,25 %, 1,09 %; in the rhizomes with roots – 0,53 %, 0,44 %, 0,51 % respectively. Using the spectrophotometric method we defined the quantitative content of phenolic substances in the drumstick primrose, Julia’s primrose, rock primrose as follows: amount of phenolic compounds (in the leaves – 5,20 %, 5,06 %, 5,47 %; in the flowers – 4,98 %, 4,90 %, 6,24 %; in the rhizomes with roots – 1,11 %, 1,46 %, 0,87 %); amount of hydroxycinnamic acids (in the leaves – 4,20 %, 3,96 %, 6,24 %; in the flowers – 3,74 %, 4,63 %, 4,98 %; in the rhizomes with roots – 2,01 %, 1,49 %, 2,40 %); amount of flavonoids (in the leaves – 4,64 %, 3,91 %, 2,19 %; in the flowers – 4,32 %, 3,85 %, 3,06 %; in the rhizomes with roots – 0,08 %, 1,09 %, 0,29 %); tannins (in the leaves – 2,35 %, 1,61 %, 2,38 %; in the flowers – 1,80 %, 1,46 %, 2,38 %; in the rhizomes with roots – 1,64 %, 1,11 %, 1,64 %); polyphenols (in the leaves – 8,01 %, 7,43 %, 8,95 %; in the flowers – 7,94 %, 7,21 %, 8,86 %; in the rhizomes with roots – 7,32 %, 5,24 %, 7,35 %) respectively. In the drumstick primrose, Julia’s primrose and rock primrose flowers we have determined quantitative content of anthocyanins – 1,08 %, 1,12 %, 0,95 % respectively. By the method of high-performance liquid chromatography (HPLC) in the three research objects revealed the qualitative composition and quantitative content of individual phenolic compounds: components of tannins, flavonoids, coumarins and hydroxycinnamic acids. The GC/MS method have determined qualitative and quantitative content of mono sugars and sucrose. Predominant in the all objects is related D-glucose. By the HPLC method studied the amino acid content of drumstick, Julia’s and rock primroses leaves and rhizomes with roots. Among the essential amino-acids in the leaves of researches objects glutamic acid prevails, among the nonessential – leucine. In the rhizomes with roots arginine quantitatively prevails. By the GC/MS method for the over ground and underground organs of drumstick primrose, Julia’s primrose, rock primrose was found the presence of fatty acids. Predominant in the drumstick primrose leaves is α-linolenic acids, in the drumstick primrose flowers and rhizomes with roots, in the Julia’s primrose leaves, flowers and rhizomes with roots, in the rock primrose leaves and rhizomes with roots – linoleic acid. Using the spectrophotometric method, we have established the quantitative content of saponins in the leaves and underground organs of drumstick, Julia’s and rock primroses, that was 0,61 %, 1,79 %, 0,32 % and 0,98 %, 0,45 %, 1,54 % respectively. The systematic macro- and microscopic analysis of drumstick, Julia’s and rock primroses stem, flower, leaf and rhizomes with roots was conducted at the first time and main diagnostic features of their morphological and anatomical structure were determined. Dense extracts from drumstick primrose leaves and rhizomes with roots were obtain. The safety of these extracts was determined: after the acute toxicity investigation they were referred to the V class of the substances toxicity according to K. К. Sidorov classification (practically nontoxic substances – LD50 ≥ 5000 mg/kg). Antiexudative activity of dense extracts from drumstick primrose leaves and rhizomes with roots was determined, and the highest activity was shown by the dense extract of drumstick primrose leaves at a dose 200 mg/kg, which was 31.6%. A distinct expectorant activity was investigated in a dense extract from drumstick primrose rhizomes with roots at a dose of 200 mg/kg, which was similar to the activity of the reference drug drops "Gedeliks" (45,0% and 44,6%, respectively). The antimicrobial activity of the obtained substances was investigated. It is proved that the pronounced bactericidal action exhibits a dense extract of drumstick primrose leaves with respect to Staphylococcus aureus, Staphylococcus epidermidis and Corynebacterium spp. The projects of quality control methods for the new medicinal plant raw materials and substances obtained from the leaves and rhizomes with roots of drumstick primrose were elaborated.
Фармакогностическое исследование культивируемых видов рода Primula L.
Pharmacognostical research of cultivated species of the genus Primula L.
Keywords: рід Primula L.; фармакогностичне дослідження; густий екстракт; протизапальна; відхаркувальна; антимікробна активність; род Primula L.; фармакогностическое исследование; густой экстракт; противовоспалительная; отхаркивающая; антимикробная активность; genus Primula L.; pharmacognostical study; dense extract; antiinflammatory; expectorant; antimicrobial activity